Evaluation of the Effect of Changing the Normalised Appointment Mode During the Coronavirus Disease 2019 Epidemic on the Development of Day Surgery - Li B; Fan X; Xia Q (Patient Preference and Adherence, 2022)
Bangju Li, Xizhen Fan, Qun Xia Day Surgery Ward, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001 People’s Republic of ChinaCorrespondence: Xizhen Fan, Day Surgery Ward The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, 230001, People’s Republic of China, Tel +86-0551-62283316, Email 1014958512@qq.comObjective: To investigate the effect of changing the normal appointment mode on day surgery.Methods: From December 2020 to December 2021, 302 patients with day surgery admitted to the hospital by using the unified reservation mode of the intelligent bed system were selected as the experimental group, while 302 patients with day surgery admitted to the hospital by using the decentralised bed reservation mode were randomly selected as the control group. The same-day surgery cancellation rate, bed utilisation rate and patient satisfaction were analysed and compared between the two groups.Results: The treatment experience of the patients in the experimental group was higher than that in the control group. The same-day surgery cancellation rate was lower than that of the control group, with a statistically significant difference (P < 0.05).Conclusion: The unified computer reservation mode of the intelligent bed reservation system is superior to the decentralised reservation mode across departments. A daytime intelligent bed reservation mode was adopted for unifying bed appointments, which could effectively reduce the same-day cancellation rate of day surgery, improve bed utilisation and improve patient satisfaction.Keywords: COVID-19, day surgery, surgical cancellation rate, patient satisfaction, evaluation